2016
DOI: 10.2134/agronj2015.0547
|View full text |Cite
|
Sign up to set email alerts
|

Root and Shoot Responses of Summer Maize to Waterlogging at Different Stages

Abstract: The specially designed soil columns experiment was conducted to determine effects of waterlogging for 6 d at the third leaf stage (V3), the sixth leaf stage (V6), and the 10th day after the tasseling stage (10VT) on root growth and development of summer maize (Zea mays L.). Results showed that waterlogging significantly decreased root length, root length density, and number of root tips compared to the control (CK). Waterlogging significantly reduced the total absorption area and active absorption area with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 24 publications
3
57
1
Order By: Relevance
“…Oxygen deficiency and presence of phytotoxins reduce root growth and formation and promote root decay. Waterlogging for six days significantly decreased root length, root length density, and the number of root tips compared to those of the control in corn plants at the V3, V6, and 10 days after VT growth stages [10]. Waterlogging conditions can decrease root conductance for water and nutrient uptake, causing nutrient deficiency and resulting in poor plant growth [11,12].…”
mentioning
confidence: 99%
“…Oxygen deficiency and presence of phytotoxins reduce root growth and formation and promote root decay. Waterlogging for six days significantly decreased root length, root length density, and the number of root tips compared to those of the control in corn plants at the V3, V6, and 10 days after VT growth stages [10]. Waterlogging conditions can decrease root conductance for water and nutrient uptake, causing nutrient deficiency and resulting in poor plant growth [11,12].…”
mentioning
confidence: 99%
“…Due to the waterlogged conditions, roots are not able to exploit a large soil volume and tend to grow near the soil surface (Sairam, Kumutha, Ezhilmathi, Deshmukh, & Srivastava, 2008). Ren, Zhang, Dong, Liu, and Zhao (2016) reported that root length, root length density, and the number of root tips in corn decreased with 6 d of waterlogging at the V3 (corn plant with three leaves), V6, and 10 d after VT (tasseling) growth stages when compared to the nonwaterlogged control. Flooding stress on 2‐d‐old soybean plants significantly suppressed fresh root weight, whereas glycolysis, fermentation, stress, and cell wall‐related protein synthesis were increased (Oh & Komatsu, 2015).…”
Section: Crop Production Losses Due To Soil Waterloggingmentioning
confidence: 99%
“…Singh and Ghildyal (1980) reported that soil flooding of corn at V6 was more harmful than at the VT growth stage. Corn in later vegetative or reproductive growth stages (V7, VT, R1) were less susceptible to soil waterlogging damage compared to early growth stages (V2) when the growing point was still below or close to the soil surface (Ren et al., 2014; Ren et al., 2016; Ritter & Beer, 1969; Zaidi, Rafique, Rai, Singh, & Srinivasan, 2004). Ren et al.…”
Section: Factors Affecting the Extent Of Waterlogging Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Waterlogging often occurs where rainfall is substantial, soil drainage is poor and the high-water level fluctuates strongly. In the Huang-huai-hai Plain, most rainfall occurs during growing season of summer maize, and yield and growth of summer maize are significantly affected by excessive rainfall and/ or flooding (Ren, Zhang, Dong, Liu, & Zhao, 2016a;Ren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%